2020
DOI: 10.1007/s10877-020-00574-z
|View full text |Cite
|
Sign up to set email alerts
|

Artifacts annotations in anesthesia blood pressure data by man and machine

Abstract: Physiologic data from anesthesia monitors are automatically captured. Yet erroneous data are stored in the process as well. While this is not interfering with clinical care, research can be affected. Researchers should find ways to remove artifacts. The aim of the present study was to compare different artifact annotation strategies, and to assess if a machine learning algorithm is able to accept or reject individual data points. Non-cardiac procedures requiring invasive blood pressure monitoring were eligible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Pasma et al . 13 compared the algorithmic and manual annotation of artifacts in arterial blood pressure signals during anesthesia. There was a significant discrepancy among the direct observation of the artifacts and the retrospective analysis or the detection using machine learning algorithms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pasma et al . 13 compared the algorithmic and manual annotation of artifacts in arterial blood pressure signals during anesthesia. There was a significant discrepancy among the direct observation of the artifacts and the retrospective analysis or the detection using machine learning algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the artifacts originating from disconnection of the monitors and from technical issues, there are several situations common in an intensive care unit that can distort the waveforms and values (patient positioning, coughing, etc.). Previous studies have investigated the pattern 8 and the origin 9 of the artifacts in the arterial blood pressure signal; some studies have also attempted to detect them 10 13 or even to eliminate them 9 , 14 , mainly using artificial intelligence tools and neural networks.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting study on artifact detection in vital signs time series was conducted by Pasma et al [ 28 ]. In the study, two trained research assistants observed in a live setting the arterial blood pressure waveform for at least one hour in 88 surgical procedures and annotated artifacts.…”
Section: Artificial Intelligencementioning
confidence: 99%
“…The authors concluded that the overall performance remained moderate. It is not new that advanced algorithms have trouble in annotating artifacts, but the most important finding of the study is probably that “it is not only important to describe who annotated data, but also when and how data points were marked as artifacts, in order to make research reproducible” [ 28 ]. Automated or manual artifact rejection in the retrospective analysis of large datasets may be prone to a similar, unsolvable artifact issue, because information about the clinical context is not recorded in most datasets available for retrospective analysis.…”
Section: Artificial Intelligencementioning
confidence: 99%
“…Although we used an automated process, it is still time-consuming and presumable also still imperfect. 61 Second, anesthesia record-keeping systems still collect large amounts of free-text data, that is unstructured and often filled with spelling mistakes. Although filtering can also be partly automated, cleaning free-text data is very time-consuming.…”
Section: The Utopia Of Large Database Studiesmentioning
confidence: 99%